Pertanggungjawaban Pidana Terhadap Pelaku Tindak Pidana Pencurian Dengan Pemberatan (Studi Putusan Nomor: 532/Pid.B/2024/PN.Tjk) - Nurkhalifah, Siti; Limantara, Benny Karya (SAKOLA: Journal of Sains Cooperative Learning and Law, 2025)
Theft is a criminal act related to a person's property. This crime is the type of crime that most often occurs in everyday life. Aggravated theft is a form of crime against property that has an impact on each victim, both psychologically and materially. As in the case of Decision Number: 532 / Pid.B / 2024 / PN.Tjk, the Decision discusses the application of criminal law in accordance with the principles of justice and legal certainty. As in this study aims to analyze a form of criminal responsibility for perpetrators of aggravated theft as regulated in Article 363 of the Criminal Code and also the judge's considerations in passing a verdict on the perpetrator of aggravated theft in the case. The research methodology used in this study is to use a normative and empirical juridical approach. Data collection through library research and field research. Data sources are obtained from court decisions and data collection techniques are carried out through research and interviews to obtain information and also answers to the main problems of the research.